TAXONOMIC CHARACTERIZATION, ANTIMICROBIAL ACTIVITY AND ANTIOXIDANT POTENTIAL OF RARE ACTINOBACTERIUM ISOLATED FROM MANGROVE ECOSYSTEM OF MACHILIPATNAM, ANDHRAPRADESH, INDIA - CH, CHIRANJEEVI; M, VIJAYALAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the present study is to isolate, characterize the potent actinomycete strain from mangrove habitats of South coast of Andhra Pradesh (Machilipatnam), India. Methods: The samples collected from mangrove niches were pretreated with calcium carbonate, diluted, Plated on Starch casein agar, Humic acid vitamin agar and yeast extract malt extract dextrose (YMD) agar media to isolate actinomycetes. The three selective media were supplemented with clotrimazole (25 μg/mL) and streptomycin (25 μg/mL) to inhibit the growth of fungi and bacteria. Results: A total of ten actinobacterial strains were isolated and designated as VLCH-1 to VLCH-10. All of them were screened and evaluated for their antimicrobial and antioxidant properties. Among them, one strain VLCH-6 was found to be potent as it exhibited high antimicrobial potential and it was identified as Pseudonocardia parietis VLCH-6 through polyphasic taxonomy (GenBank accession number: MZ951166). The growth profile of the strain was studied by culturing it in YMD broth. The culture broth extracted with ethyl acetate was tested for antimicrobial assay and found to be active against Escherichia coli, Xanthomonas campestris and Aspergillus niger. The antioxidant potential of the strain VLCH-6 was evaluated by 2,2- diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity. In the screening, the culture extract exhibited strong antioxidant activity against DPPH free radicals. Conclusion: Over all, it was evident from the present study that mangrove habitats of Machilipatnam serve as a good source for potent actinomycetes possessing broad spectrum of antimicrobial and antioxidant metabolites.